In-Situ Electrochemical Transmission Electron Microscopy for Battery Research. (23rd April 2014) - Layla Mehdi, B.; Gu, Meng; Parent, Lucas R.; Xu, Wu; Nasybulin, Eduard N.; Chen, Xilin; Unocic, Raymond R.; Xu, Pinghong; Welch, David A.; Abellan, Patricia; Zhang, Ji-Guang; Liu, Jun; et al.
Abstract The recent development of in-situ liquid stages for (scanning) transmission electron microscopes now makes it possible for us to study the details of electrochemical processes under operando conditions. As electrochemical processes are complex, care must be taken to calibrate the system before any in-situ/operando observations. In addition, as the electron beam can cause effects that look similar to electrochemical processes at the electrolyte/electrode interface, an understanding of the role of the electron beam in modifying the operando observations must also be understood. In this paper we describe the design, assembly, and operation of an in-situ electrochemical cell, paying particular attention to the method for controlling and quantifying the experimental parameters. The use of this system is then demonstrated for the lithiation/delithiation of silicon nanowires.